Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

If ( 2x - 3y = 6 ) and ( x - 6y = 12 ), then find the value of x and y.​

Sagot :

2x-3y=6—eq(1)
x-6y=12—eq(2)
from eq 2
x= 6y+12
then replacing it in eq 1
2(6y+12)-3y=6
12y+24-3y=6
9y=-18
y=-2
then x=6(-2)+12
x=0